Benefits of international trauma rotation in South Africa: comparison with a trauma center in Tokyo. Issue 4 (26th September 2022) - Nagao, Tsuyoshi; Nakahara, Shinji; Fujita, Takashi; Sakamoto, Tetsuya; Steyn, Elmin
Abstract: International rotations have been an option for young surgeons who face difficulties in obtaining sufficient trauma training in their own countries. One of the authors attended training in trauma surgery in South Africa for 6 months, where there are many trauma caseloads, and could experience the number of emergency operations equivalent to approximately 5 years in Japan. The rotation allows trainees to expose clinical practices intensively and to learn principles and theories of care under experienced academic surgeons. On the other hand, they could contribute to the host hospital as part of the workforce and by assisting young surgical residents. the development of a more systematic and formalized framework for staff exchange between developed and developing countries will provide mutual benefits to both sides.